Reflection Of The Use Of Intranet To Improve The Performance Of Electronic Governance An Exploratory Study Of The Ministry Of Higher Education And Al-Karkh Education Directorate - et. al., Hussein Hamed Khudair Jinah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The presence of a strong internal guaranteed and secure intranet with good specifications is the important factor in improving the performance of the institution and establishing a good system to start work with electronic governance, a basic and supportive indicator to strengthen comprehensive audit and optimization of available resources practiced by boards of directors or organizations according to the style and style of the institution chosen to run its affairs when preparing an organization with a secure and discreet internet network with global specifications, equipped with efficient and reliable information and communication systems that reassure the network users of relying on them to walk their administrative affairs and raise the level of the organization's performance by facing the risks that prevent the achievement of the objectives of the Organization. The internal network framework is also considered to provide all the requirements, electronic devices, modern communication equipment with high-quality technology and a practical and programmatic design that reduces the burden of administrative costs and strengthens the internal administrative system with its control auditing and reformative software systems with the ability to accelerate the completion of the work and archive it electronically and lack of storage and provide space and reducing space its size. In this study, the researchers discussed the necessity of employing the internal internet for the sustainability and stability of the management system for its institutional resources in order to reach its goals in the best ways, time and costs, and electronic governance that seeks to continuously adapt to the work environment and adapt to the challenges of the current era by programming the work of the departments and administrative divisions.